CORRELATION BETWEEN PROJECT-BASED LEARNING ACTIVITIES AND STUDENTS' ATTITUDES TOWARDS THE SUBJECT OF MATTER AND ENERGY - Arif, Rifda Nur Hikmahwati (BIOCHEPHY: Journal of Science Education, 2025)
This study aims to determine the correlation between project-based learning activities and students' attitudes in the subject of matter and energy. This study is a descriptive correlative study with a quantitative approach. The population of the study was all students of the subject of matter and energy in the even semester of the 2024/2025 academic year in the Science Education Study Program, FMIPA UNM. The sampling technique used was saturated sampling. The data collection technique was carried out using an observation sheet of project-based learning activities and student attitudes that had been tested for validity and reliability. The data analysis technique used descriptive statistics and inferential statistics to determine the correlation between student activities and attitudes in the subject of matter and energy. The results of the study showed that: 1) The level of project-based learning activities of Regular A class students was 78.04 in the high category, Regular B class was 75.05 in the high category, and ICP class was 78.13 in the high category. 2) The attitude level of Regular A class students is 73.28 in the high category, Regular B class is 75.14 in the high category, and ICP class is 75.00 in the high category. 3) There is a very strong and significant correlation between project-based learning activities and student attitudes in the three classes studied (correlation coefficient > 0.81). This study confirms that increasing activity in project-based learning has a positive effect on the formation of student attitudes that support the learning process.